Fluctuating Light Takes Crop Photosynthesis on a Rollercoaster Ride . Issue 2 (18th October 2017) - Kaiser, Elias; Morales, Alejandro; Harbinson, Jeremy
Abstract : Crops are regularly exposed to frequent irradiance fluctuations, which decrease their integrated CO2 assimilation and affect their phenotype.